Penerapan Metode Chemical Cleaning Guna Meningkatkan Kualitas Produk SWRO Pada Sistem Reverse Osmosis PLTGU Tambak Lorok - Prayudi Prayudi; David Ariyanto (JURNAL POWERPLANT, 2014)
Reverse Osmosis systems at Pond PLTGU Lorok is a system that has the principle of using a micro filtration membrane. Applying the theory behind the osmotic pressure which will be filtered sea water into fresh water. Reverse Osmosis system in the absence of biocide chemical injection system which serves to prevent the formation of organic fouling in membrane. In the SWRO system using a feedwater in the form of sea water where a lot of particulate matter contained therein. If the particulate escaped from pretreatment system will be able to clog the membrane. So that the flow rate will reduce the yield of the product as well as increase the value of the product konduktivity SWRO. In order to improve its quality, it is necessary to dissolve Chemical Cleaning foulant attached to the membrane. From the results of the Chemical Cleaning has been done then obtained an increase in the flow of products SWRO of 27 liters / minute.